Muṟṟuppeṟāta vivātaṅkaḷ - Nuḵmāṉ, M. A. (Kālaccuvaṭu Patippakam, 2023)
Chiefly on Tamil literature from Sri Lanka; includes on ethnic relations and violence
Keywords: Interview; Nuk̲amān̲; Em. Ē; Tamil literature